High-frequency multibeam echo-sounder measurements of seafloor backscatter in shallow water: Part 2 - Mosaic production, analysis and classification - Parnum, Iain; Gavrilov, Alexander (Society for Underwater Technology, 2011)
Backscatter measurements collected with high-frequency multibeam echo-sounders (MBES) have been used to map the spatial distribution of seafloor types and properties in shallow waters. The methods for collection and processing of MBES backscatter data were considered in Part 1 – Data acquisition and processing (Parnum and Gavrilov, 2011), published alongside this paper. The aim of Part 2 is to describe the main methods used to produce backscatter maps of the sea floor free from angular artefacts, and to classify seafloor types based on backscatter and bathymetry analysis. These methods are illustrated using a dataset collected with a Reson SeaBat 8125 MBES in Esperance Bay in Western Australia, although the methods and errors discussed are relevant to other high-frequency shallow-water MBES.